2018
DOI: 10.1200/jco.2018.36.30_suppl.303
|View full text |Cite
|
Sign up to set email alerts
|

Real-time assessment of resource utilization and subsequent cost analysis in cancer patients (pts) near the end of life (EOL).

Abstract: 303 Background: Aggressive medical interventions and associated high costs of care for cancer pts near the EOL are common. Addressing this issue at the local level requires an accurate, automated process to merge real-time clinical EHR data with cost data for performance reporting. Methods: This was a single-center, observational cohort study of decedents treated with anticancer therapy (antiCT) in the last 6 months of life from January 2016 to October 2017. Pts were stratified by antiCT use in the last 30 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…One study suggests that any SACT at EOL, including immunotherapy, is associated with higher rates of downstream acute care, delayed hospice care, and higher costs . This finding requires future research to examine the association of immunotherapy at EOL with downstream acute care use and quality of life in a larger, more representative sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study suggests that any SACT at EOL, including immunotherapy, is associated with higher rates of downstream acute care, delayed hospice care, and higher costs . This finding requires future research to examine the association of immunotherapy at EOL with downstream acute care use and quality of life in a larger, more representative sample.…”
Section: Discussionmentioning
confidence: 99%
“…Use of systemic anticancer therapy (SACT) at end of life (EOL) is associated with increased acute care use, delayed goals-of-care conversations, late hospice enrollment, higher costs, and possibly adverse quality and duration of life . In 2012, the American Society of Clinical Oncology and the National Quality Forum developed the quality measure Proportion Receiving Chemotherapy in the Last 14 Days of Life to promote reduction in chemotherapy and earlier integration of palliative care at EOL.…”
mentioning
confidence: 99%
“…5,6 Two recent studies suggest that continuing CPI or targeted therapies past the point of futility is associated with higher rates of acute care utilization. 2,7 Thus, understanding the factors associated with this practice is critical to developing future interventions to curtail it. Patient factors included race, 8,9 insurance type, 9 and Eastern Cooperative Oncology Group (ECOG) PS.…”
Section: Introductionmentioning
confidence: 99%
“…Use of systemic treatment at the end of life (EOL) is by definition futile and is highly correlated with EOL emergency department, hospital and intensive care unit utilization, late transition to hospice, death in the acute care setting, and higher costs. 1,2 This pattern leads to distress among patients and caregivers. In 2012, ASCO and the National Quality Forum (NQF) developed a quality measure with the goal of reducing chemotherapy within 14 days of death.…”
Section: Introductionmentioning
confidence: 99%
“…1 Initially, the focus was to provide earlier palliative care (conversation around goals of care and hospice enrollment), as no benefit had been observed among patients receiving chemotherapy at the EOL. 2,3 Studies have shown that patients receiving palliative chemotherapy at the EOL do not live longer, and their quality of life was impaired because of unnecessary toxicities. 1-4 In early 2000s, indicators of quality EOL care were identified, including administration of systemic therapy, hospital admission, ICU admission, > 1 emergency department visit within the last 30 days of life, in-hospital death, and hospice initiation within the last 30 days of life.…”
mentioning
confidence: 99%